Relationship Factors Associated With Early Adolescent Dating Violence Victimization and Perpetration Among Latinx Youth in an Agricultural Community - Boyce, Sabrina C. (Journal of interpersonal violence, 2022)
Latinx early adolescents within the United States are particularly vulnerable to dating violence; yet, little research has examined early dating experiences and violence outside large urban settings. Latinxs, in particular, may experience a unique window of opportunity for dating violence (DV) prevention during early adolescence, based on their trends in risk behavior over the adolescent period. This study extends the current research on dating violence by examining a highly understudied population, Latinx early adolescent girls and boys residing in an agricultural community, by assessing victimization and perpetration, and examining interpersonal-level factors as potential risk and protective factors for violence. Using data from a prospective cohort study of Latinx adolescents with relationship experience (past six months) (N = 296; girls: n = 147; boys: n = 149; mean age: 13.8), we assessed the association between dating relationship characteristics and dating violence victimization and perpetration using modified-Poisson regression models with robust standard errors stratified by gender. In multivariable analyses, we found that girls with gang-affiliated partners, partner-related withdrawal from friends, and girls who had used drugs or alcohol with a partner experienced greater risk for dating violence. Additionally, holding beliefs supportive of female sexual naivete and engaging in and communicating about sexual activity were associated with victimization among girls. No significant associations were found among boys. Findings affirm the need for multilevel DV prevention programming that starts in middle school and addresses social isolation, gang exposure, and traditional Latinx gender-norm beliefs regarding marianismo. These findings underscore the imperative to coordinate dating and gang violence prevention efforts by addressing common co-occurring interpersonal and environmental risk factors, including social isolation and culturally-specific traditional beliefs. Such factors could also assist providers, families, and peers in early identification of Latinx early adolescents at risk for DV, especially in rural contexts where resources are often limited.